A new species from the eastern Amazon rainforest with lectotype designations and key for Brazilian Oxarthrius Reitter, 1883 (Coleoptera: Staphylinidae: Pselaphinae) - Gouvea, Bruno; Valente, Roberta M.; Asenjo, Angélico (Zootaxa, 2023)
Oxarthrius spiculatus sp. nov. from the Brazilian Amazon is described. Major diagnostic features of male and female genitalia are illustrated. Female genitalia is described for the genus for the first time. The specimens of the new species were collected from bauxite mining area in the State of Pará, Brazil where they seem to live in leaf litter. The distribution of the genus is covered and a key to the known Brazilian species is given. Additionally, the lectotype is designated for the Brazilian species Oxarthrius anthicoides (L.W.Schaufuss) and Oxarthrius bispinosus (Reitter).